Analysis of the Histopathology, TNF-α of Microglia Cells Expression, NRG-1/erbB Oligodendrocyte, and Ki67/Apoptosis of Dentate Gyrus Rattus novergicus Brain After Acute Traumatic Brain Injury - Wibi Riawan; Putri Fitri Alfiantya; Oktavia Rahayu Adianingsih; Zulkarnaen Zulkarnaen; Alif Fariz Jazmi; Sitti Ayu Hemas N. (Indonesian Journal of Cancer Chemoprevention, 2015)
Head trauma or traumatic brain injury (TBI) gives most serious impact on the central nervous system. Several experimental models have been established to mimic different pathogenesis characteristics of TBI. The purpose of this study was to determine whether there is evidence of hystopathological lesions in the brain tissue after Marmorou TBI models. This study uses Rattus norvegicus Sprague Dawley strain. Macroscopic and microscopic observations on the brain tissue were done. Macroscopic lesions were observed in the brain. Microscopic observation was performed with Haematoxylin-Eosin (HE) staining and immunohistochemistry on the distribution of microglia cells and pyramidal cells in the cortex. Meanwhile, the distribution of NRG-1/ErbB, proliferation, and apoptosis were observed in the hippocampus. The results of macroscopic observation showed that there were wounds caused by falling loads and vasodilatation. On microscopic observation, the TBI group showed an increase in neutrophils distribution and distribution of activated microglia to produce TNF-α, and decrease in the number of cortical pyramidal cells significantly. The distribution of NRG-1 tended to decrease after exposure of TBI and had no effect on its receptor, erbB. Exposure of TBI appears to lower the activity of neuronal cells proliferation in dentate gyrus (DG) area and significantly increase the number of apoptotic cells. Marmarou model is a physiological model of TBI that spontaneously occurs following a trauma to the head, for example trauma due to an accident. This data can be used as a preliminary data of inflammation and tissue regeneration of disrupted adult brain. Therefore, this research could be used as the basis in the studies of therapeutic agents in the process of neurogenesis of brain cells.Keywords: traumatic brain injury, ERG-1/ErbB, dentate gyrus, Ki67, TNF-a, microglia